Respostas

2014-06-09T01:06:02-03:00
A)x²-4x=0   onde a= 1  b=-1 c=0


Δ=b²-4.a.c
Δ=(-1)²-4.1.0
Δ=1-0
Δ=0   raiz de 0 é 0

x'=-(-1)+0     +1+0    1
   ¨¨¨¨¨¨¨¨¨¨¨+ ¨¨¨¨¨¨¨¨¨¨= ¨¨¨¨
        2.1         2        2


x"=-(-1)-0      +1-0     1
     ¨¨¨¨¨¨¨¨¨¨ = ¨¨¨¨¨¨¨¨= ¨¨¨¨
         2.1         2       2                         S:(1/2, 1/2)



b)x²-5x=0            0nde a=1 b=-5  c=0

Δ=b²-4.a.c
Δ=(-5)²-4.1.0
Δ=25-0
Δ=25   raiz de 25 é 5

x'=-(-5)+0   +5       5
    ¨¨¨¨¨¨¨¨¨¨+ ¨¨¨¨¨¨=¨¨¨¨¨¨
         2.1      2       2                        S:(5/2, 5/2)




c)16x²-36x=0    0nde a=16   b=36   c=0

Δ=36²-4.1.0
Δ=1296-0
Δ=1296      raiz de 1296 é 36


x'=-36+0     -36
 ¨¨¨¨¨¨¨¨¨¨¨¨=¨¨¨¨¨¨¨= -18
      2.1        2                           S:(-36, -36)




d)6x²-54=0   onde a=6 b=0 c=-54

Δ=0²-4.6.54
Δ=0-1296
Δ=1296   raiz de 1296 é 36


x'=0 + 36    36
   ¨¨¨¨¨¨¨¨¨¨ = ¨¨¨¨¨¨ = 3
        2.6      12              S:(3, -3)
 



e)15x²-60x=0    onde a=15  b=-60  c=0

Δ=(-60)²-4.15.0
Δ=3600-0
Δ=3600   raiz de 3600 é 60


x'=-(-60)+60      +60+60  120
    ¨¨¨¨¨¨¨¨¨¨¨¨¨¨ = ¨¨¨¨¨¨¨¨¨¨¨¨=¨¨¨¨¨¨=4
        2.15            30       30


x"=-(-60)-60     +60-60      0
  ¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨=¨¨¨¨¨¨¨¨¨¨¨¨=¨¨¨¨¨¨= 0                 S:(4, 0)
          2.15          30       30



f)25x²-36=0   onde a=25  b=0  c=-36


Δ=0²-4.25.(-36)
Δ=0 + 3600
Δ=3600   raiz é 60



x'=0²+60      60¨   30¨    6
 ¨¨¨¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨¨= ¨¨¨¨=¨¨¨¨¨¨     simplificado
      2.25      50     25     5


x"=0²-60   -60    -30¨      6 
  ¨¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨= ¨¨¨¨¨¨= - ¨¨¨¨¨¨
      2.25    50     50       5                       S:(6/5, -6/5)





g)12x²-20x=0   0nde a=12   b=-20   c=0

Δ=(-20)²-4.12.0
Δ=400-0
Δ=400  raiz é 20


x'=-(-20)+20       +20+20    40      10     5
 ¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨¨¨=¨¨¨¨= ¨¨¨¨¨¨
        2.12              24        24       6      3



x"=-(-20)-20          +20-20     0
  ¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨¨= 0
        2.12             24           24                      S:(5/3, 0)